An Evaluation on Computer Science and Engineering Education Based on User Interface (UI) (International Journal of Food and Nutritional Sciences, 2022)
User Interface (UI) describes the visually appealing elements of an application or an online class which people may engage with. Webpage (or slide) patterns, navigation bar, as well as any menus are all included in this. Cyber learning settings are widely available and are being used more often, although more study is still needed to determine their value in undergraduate education, especially in STEM education system. Furthermore, utility assessors do not agree on any standards. The authors of this article provide a range of studies that may be utilized to analyses the utility of a cyber-learning platform in the development and software field of engineering, utilizing experience for users as well as consumer experience evaluation to determine its effectiveness. The present study focuses on the evaluation of computer science and engineering environments with the help of User Interface (UI). The findings of this study will drive future studies on the creation of cyber learning platforms for digital literacy and suggest improvements to the Software Engineering as well as Development of Cyber Educational Setting.